EFEKTIVITAS KAMPANYE TAGLINE “OPTIMIS JATIM BANGKIT” PADA POSTINGAN INSTAGRAM @humasprovjatim (PERIODE AGUSTUS-OKTOBER 2022) (The Commercium, 2023)
The purpose of this research is to determine the effectiveness of the "Optimis Jatim Bangkit" tagline campaign strategy on@humasprovjatim Instagram posts between August and October 2022. The strategy used in this research is the surveymethod. Among them, this research chooses quantitative analysis. The study will be conducted on the @humasprovjatimInstagram account and the survey will be distributed via Google Forms to followers of the @humasprovjatim Instagramaccount. The population in this research is the followers of the @humasprovjatim Instagram account. The sample of thisresearch will be taken from followers' who actively like and comment on 68 posts of the @humasprovjatim Instagram accountthat use the tagline "Optimis Jatim Bangkit" during the period August-October 2022. The result of this research is theaverage score on the variable Effectiveness of the Tagline Campaign "Optimis Jatim Bangkit" on Instagram Posts@humasprovjatim (August - October 2023 period) obtained the final weight of the EPIC rate value is 4.10 which if enteredinto the rating scale is included in the effective category. It can be said that the Tagline Campaign "Optimis Jatim Bangkit"on Instagram Posts @Humasprovjatim (Period August - October 2023) is effective in increasing public empathy or trustthrough the tagline campaign "Optimis Jatim Bangkit" on the account's Instagram posts, influencing the level of publicinterest in interpreting the tagline "Optimis Jatim Bangkit”, Making the tagline "Optimis Jatim Bangkit" from the East JavaProvincial Government more prominent than other regional taglines, and high public understanding and the strength of theimpression conveyed by the tagline campaign "Optimis Jatim Bangkit"